AN INVESTIGATION OF THE FLUCTUATION IN LANGUAGE LEARNING MOTIVATION OVER TIME: A QUALITATIVE CASE STUDY - Alzahrani, Mona (PEOPLE: International Journal of Social Sciences, 2024)
In SLA, the variation of motivation when learning a language is a significant research area (Kikuchi, 2015). It has been established that motivation fluctuates, and that high and low levels of motivation alternate during language learning cycles (Albalawi & Al-Hoorie, 2021; Kikuchi, 2015, 2019). This research aims to comprehend and investigate the complexity of motivation fluctuation across language learning experiences which involves demotivation and remotivation. It focuses on the language learning motivation fluctuations of female students who studied general English in Saudi Arabia for more than six years at the school level up until their first year of university at the age of nineteen. It considers the dynamic and changing nature of motivation and its context-specific nature. It explores motivation fluctuation with broad perspective considering typical and atypical, academic, and non-academic as well as internal and external factors that lead to language learners’ demotivation in English language learning and the demotivation process. It also explores how language learners get remotivated after experiencing demotivation in language learning, including factors, opportunities, and challenges. To help understand this transient nature and process, this research adopts a qualitive design and will utilize thick data captured through narrative inquiry. It aims to capture language learners’ motivation fluctuation, their loss of that motivation, as well as their regaining of it. The term "language learner" describes a person who is consciously involved in the process of acquiring, developing, or improving their skill in one or more languages that can be considered foreign or second languages and may take place in formal settings like universities and institutions or through independent study utilizing alternative resources ​(Littlewood, 1984)​.